Assessment of skills, knowledge and training for buildings maintenance managers in Kuantan, Pahang - Nor Laily, Mat Aris (2010)
The research investigated the maintenance building managers in public buildings in Kuantan, Pahang and in the process, identified the essential skills,knowledge and training for maintenance managers in buildings. A total of 40 questionnaires was distributed to the maintenance staff and used for study. The survey covered six public buildings in Kuantan, Pahang Based on researched, most of the managers of public buildings do not have access to any formal training on effective use of building facilities. The most important skills considered necessary for an effective maintenance managers in executing maintenance operations in public buildings according to the study are professional experience, intelligence, good communication, good qualification and human relation skill. Based on the above findings, the study recommends that management should ensure that the head of maintenance department has the required maintenance managers' attitude success factors before appointing them rather than being political in their selection. Management should ensure that both the management and all the staffs are given adequate training for effective use of the building and the services.